The Impacts of Graded Doses of Pyridoxine on the Biomarkers, Aspartate Aminotransferase, lactate Dehydrogenase and Total Antioxidant Capacity in Doxorubicin-Induced Cardiotoxicity in Female Rats - Abdul Ridha, Doaa Kadhim; Al-Shawi, Nada Naji (Iraqi Journal of Pharmaceutical Sciences, 2017)
Abstract: The aim of the current study was to investigate the possible protective effect of graded doses (5, 10, and 15mg/kg) of pyridoxine hydrochloride intraperitoneally injected against (15mg/kg) doxorubicin-induced cardiotoxicity in female rats. Fifty-six (56) Wistar albino female rats were utilized weighing 180-200 gm allocated into eight groups, seven rats each; Group I: negative control distilled water; Group II: Pyridoxine (5mg/kg); Group III: Pyridoxine (10mg/kg); Group IV: Pyridoxine (15mg/kg); Group V: doxorubicin (15 mg/kg); Group VI: Pyridoxine (5 mg/kg) prior to doxorubicin (15 mg/kg); Group VII: Pyridoxine (10 mg/kg) prior to doxorubicin (15 mg/kg); Group VIII: Pyridoxine (15 mg/kg) prior to doxorubicin (15 mg/kg). DOX caused significant elevations in serum biomarker enzymes of aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and significant reduction in heart tissue homogenate content of total antioxidants capacity (TAOC). Treatment with 15mg/kg pyridoxine for four consecutive days prior to a single dose 15mg/kg doxorubicin resulted in significant reduction in serum enzymes level of AST and LDH. Treatment with 10 or 15mg/kg pyridoxine for four consecutive days prior to a single dose of doxorubicin produced significant increments in TAOC heart tissue homogenate level compared to positive control. In conclusion, pyridoxine supplementation might be a promising adjunctive agent for improving oxidative stress and biological markers for preventing DOX-induced cardiac complications.